KARAKTERISTIK SARANG TEMPUA Ploceus philippinus (Linnaeus, 1766) DI AREA PERSAWAHAN GURUN AUR, KECAMATAN BANUHAMPU, KABUPATEN AGAM, SUMATERA BARAT - Merry, .; Novarino, Wilson; Rizaldi, Rizaldi (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
A study about the nest characteristics of baya weaver ( Ploceus philippinus ) around agricultural area in Gurun Aur, Subdistrict Banuhampu, Regency of Agam, West Sumatra, had been conducted from March to Mei 2016 using survey methods. This study aimed to describe the characteristics and materials used in building the nests. The results showed that baya weaver built their pendant-like nest mainly on coconut trees with average height 7.81 meters above ground. The nests hung on leaf stems with nest entrances faced down. Incomplete nests were also found, possibly resulting from mating failure. The form of the incomplete nests resembled dome, while the completed nests varied from oval to kidney-like. Nest sizes were also varied in term of nest length, weight and length of hooks. The baya weavers mostly used fibers from coarse grass (Graminae; Imperata cylindrica ) to build their nest and used the fine stalks of the grass to line up the chamber.